The Mechanism of Platelet Aggregation in Relation to Hemostasis - Käser-Glanzmann, R; Lüscher, E. F (Thrombosis and Haemostasis, 1962)
The finding that ADP induces the aggregation of human blood platelets is confirmed. Under the influence of thrombin platelets release enough. ADP to account for their mutual aggregation during viscous metamorphosis. Other nucleotides liberated under the same conditions are ATP and AMP. The nucleotides released from platelets during VM have been separated by chromatography and a molar ratio of ATP : ADP : AMP = 1 : 5 : 3 has been found. It is concluded that platelet aggregation by ADP in the course of the formation of the hemostatic plug is a self contained process normally independent of the presence of other blood cells.